DEVELOPMENT OF PRIMARY SCHOOLS IN THE CONTEXT OF DUAL CAREER - Parandjuks, Rihards (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The concept of dual careers is based on the principles of the Olympic Charter with harmony of the mind and body at its core. Contemporary education systems are goal-oriented and neglect their responsibility to aid in the personal development of students. The role of sports is not sufficiently emphasized in the educational process. In order to draw attention to these issues, the author has initiated a dual career development project ‘Sports class’ with the financial support of Cēsis Municipality. The project launched on September 1, 2019. The study population was grade 7a of Cēsis Secondary School enrolled in extra physical education classes. To attain the main aim of dual career of combining education and sports, all participants needed to achieve a certain average mark in academic subjects. This research aims to determine the overall results of the project in the first semester of the academic year 2019/2020. Research methods included quantitative methods (surveys) with 83 participants and qualitative methods with 5 interviewees. Data collection and analysis were done using Windows SPSS. The three dependent variables were academic results, progress in sports and personal development. The acquired data show significant progress in all variables. Thus, it is possible to recognize the positive role of sports in overall academic achievement. As a result, the scope of the project will be expanded and continued in the future.